Underestimation of creative writing in methodologies of teaching foreign language grammar - Бойко, Олена Анатоліївна; Байбекова, Людмила Олександрівна (The Journal of V.N. Karazin Kharkiv National University. Series: Foreign Philology. Methods of Foreign Language Teaching, 2021)
The article is devoted to the problem of underestimation of "writing", namely creative writing, in teaching foreign language grammar. The aim of the article is to prove the importance, expediency and demand for mastering the skill of literate creative writing in the modern world. The article presents data obtained as results of researches by leading scientists among pupils, students, adults, the employed population and job seekers, on the analysis of foreign language teaching methodologies and the introduction of creative writing in the educational process of secondary and higher education, as well as foreign language courses. The study shows that during the implementation of foreign language creative writing all students, regardless of their language proficiency, are given the opportunity to express their own visions of a certain phenomenon, using existing skills of grammar and vocabulary. Thus, creative writing provides conditions for the use of learned vocabulary and is a kind of activity less managed by the teacher, as in the process of creative writing the student looks for lexical units and selects grammatical forms relevant to the task himself. Teachers who have changed traditional methods to teaching grammar using creative writing note the effectiveness of this process and provide certain recommendations and guidelines, the main of which are described in this article. Thus, creative writing promotes individual approach to learning, helps to increase students` level of self-esteem and motivation, their thirst for public expression of their own opinion. The conclusions presented in the article convincingly testify to the need of making changes to the traditional system of teaching and bringing the methods of teaching foreign languages to a level that will meet the requirements of modern life in the period of globalization and development of international relations.